Precautionary Monetary and Fiscal Policies - Berkmen, Pelin (IMF Working Papers; Working Paper ;, 2007)
This paper explains why the debt reduction motive for countries that are subject to borrowing constraints and a volatile environment is greater than for those with a more stable environment and relatively better access to the financial markets. In particular, it shows that the possibility of losing the ability to borrow in the future induces precautionary debt reduction. When a government loses its ability to borrow, shocks are more costly to the economy, since they cannot be spread over time. The precautionary motive arises from the need to make these adjustments less painful when the borrowing constraints bind. To avoid large losses in the constrained period, the government prefers to raise taxes and inflation in earlier periods more than would be implied otherwise, leaving less debt to the future periods, and thereby shifting some of the required adjustment to the earlier periods. In other words, the coexistence of large shocks and borrowing constraints forces the government to be more prudent in its management of debt.